Prevalence and Severity of Premenstrual Syndrome among Female University Students in Central Uganda: A Cross-sectional Study - Atim, Elizabeth; Nabushawo Okecho, Florence; Ndagire, Regina; Lwanira Nassozi, Catherine (Student’s Journal of Health Research Africa, 2022)
Background Premenstrual Syndrome (PMS) is characterized by recurrent psychological, behavioural, and/or physical symptoms occurring before menses and usually resolve by the end of or during menstruation. These symptoms usually affect the women’s quality of life and efficiency. Although over 95% of women worldwide suffer from PMS, in Uganda, little is documented about the prevalence and existence of PMS among students. This study, therefore, sought to determine the prevalence and severity of PMS among female university students in Central Uganda. Methodology A cross-sectional study was carried out using a questionnaire between November 2021 and May 2022. The sample of 238 participants was taken from female students in 4 universities who met the inclusion criteria. Sampling was done by proportionate sampling. Primary data was obtained about Premenstrual Syndrome prevalence and severity using modifications of the following tools: The American College of Obstetricians and Gynecologists’ diagnostic criteria for PMS; the Diagnostic and Statistical Manual of Mental Disorders criteria (DSM-IV) diagnostic criteria for PMDD; and the premenstrual symptoms screening tool (PSST). The data was analysed to obtain descriptive statistics such as frequencies and percentages. A student was considered to be suffering from PMS if they satisfied the DSM-IV criteria for the diagnosis of PMS. Results The prevalence of PMS among female University students in central Uganda was found to be 28.3% (60). However, at least 76.9% (163) of the respondents suffered at least one or more symptoms of PMS. Conclusion Over a quarter of female university students suffer from Premenstrual syndrome. Recommendation There is a need to create awareness as well as mobilize social support so that there is help available to the students who suffer PMS.